2013
DOI: 10.1177/0004563213481586
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of single low-density lipoprotein particles by atomic force microscopy

Abstract: Background: The size of lipoprotein particles is relevant to the risk of coronary artery disease (CAD). Methods: We investigated the feasibility of atomic force microscopy (AFM) for evaluating the size of large low-density lipoprotein (LDL) and small dense LDL (sd-LDL) separated by ultracentrifugation. The measurements by AFM in tapping mode were compared to those by electron microscopy (EM).Results: There was a significant difference in particle sizes determined by AFM between large LDL (20.6 AE 1.9 nm, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…This is done by assuming that all of the LDL are spherical-like particles tightly arranged on the air/water interface with an estimated mean diameter per particle of 20 nm. This result is in good agreement with many pervious results as pointed out in the Introduction [10,27,28]. The result indicates that the size of LDL particles is not only affected by the oxidation [10] but also due to its adsorption and compression at the air/water interface; however, the compression elasticity of the LDL film is also likely to be affected by these external stimuli [13,25,26].…”
Section: Pressure-area Isotherms Of Ldl/elasticity Of Ldl Particlessupporting
confidence: 91%
See 1 more Smart Citation
“…This is done by assuming that all of the LDL are spherical-like particles tightly arranged on the air/water interface with an estimated mean diameter per particle of 20 nm. This result is in good agreement with many pervious results as pointed out in the Introduction [10,27,28]. The result indicates that the size of LDL particles is not only affected by the oxidation [10] but also due to its adsorption and compression at the air/water interface; however, the compression elasticity of the LDL film is also likely to be affected by these external stimuli [13,25,26].…”
Section: Pressure-area Isotherms Of Ldl/elasticity Of Ldl Particlessupporting
confidence: 91%
“…In their attempts to reconstruct a spherical-like model for LDL particles, they also found that the LDL diameter of the ringshaped structure roughly corresponds to the diameter of an intact LDL particle on the order of 25 nm. Other topological AFM-based studies on native-and ox-LDL particles on densely immobilized Au surfaces showed that measuring the short and long axis of the observed ellipsoid-like LDL particles lies between 20 and 30 nm [28].…”
Section: Pressure-area Isotherms Of Ldl/elasticity Of Ldl Particlesmentioning
confidence: 97%
“…LDL fraction was isolated from the serum by sequential ultracentrifugation. 26 During the ultracentrifugation, EDTA (260 µ M) was always present in the sample solution to avoid lipid oxidation. Ultracentrifugation was carried out using a near-vertical tube rotor (MLN-80; Beckman Coulter, Fullerton, CA) on a model Optima MAX (Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously, the LDLs have spherical structures with diameter of 23-26 nm. 26,32 In AFM, however, they were slightly flattened possibly due to the adsorption to the Au and/or to the bias of AFM. Although no definite change was observed in the topography between n-LDLs and ox-LDL 1 h, a few particles were enlarged among ox-LDL 3 h, as indicated by white arrows in Figure 3(d), supposedly due to denaturation and/or fusion of LDL particles.…”
Section: Topographymentioning
confidence: 99%
“…Lipoprotein fractions were isolated from serum by sequential ultracentrifugation. 32 Briefly, ultracentrifugation was performed using a near-vertical tube rotor Fifty microlitres of either the LDL sample or saline were spiked into 450 lL of serum obtained from the same subject. Five sets of the same sample were prepared.…”
Section: Influence Of Ldl-cmentioning
confidence: 99%